Correction to "Quaternionic Davis–Wielandt shell in a right quaternionic Hilbert space'', Ukrainian Mathematical Journal, vol. 75, No. 6, November, 2023 (Ukrainian original vol. 75, No. 6, June, 2023) - Jeribi, Aref; Mahfoudhi, Kamel (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5We correct a mistake made in the proof of Example 2.1. In fact $\langle T\phi,\phi\rangle_{\mathbb{H}}=0$ is not true in the case where $T=\begin{pmatrix}  \mathbf{q} & 0 \\0 & -\mathbf{q}\\\end{pmatrix}.$